2016
DOI: 10.1007/s40735-016-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Pourbaix Diagrams to Study the Corrosion Behaviour of Hardfacing Alloys Based on Chromium Carbides at 298 K (25 °C)

Abstract: The Pourbaix diagrams also known as the E-pH diagrams were constructed for hardfacing alloys based on three chromium carbides: Cr 7 C 3 , Cr 23 C 6 and Cr 3 C 2 at 298 K (25°C). Using the thermodynamic data available for the main species at 298 K (25°C), Pourbaix diagrams for the chromium carbides are constructed at a concentration of 10-6 M of aqueous species. It was found that the diagrams are able to explain the results of experimental work performed on chromium carbides in NaOH. It was found that the stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…However, Tsai et al [5] found that chromium carbide (Cr 23 C 6 ) did corrode at 300°C. Cr 23 C 6 is a less stable carbide than Cr 7 C 3 [11]. The final potential from the tests done by Salasi [6] was closely matching with that of alloy 1 in this investigation.…”
Section: Potentiodynamic and Potentiostatic Testsupporting
confidence: 73%
See 2 more Smart Citations
“…However, Tsai et al [5] found that chromium carbide (Cr 23 C 6 ) did corrode at 300°C. Cr 23 C 6 is a less stable carbide than Cr 7 C 3 [11]. The final potential from the tests done by Salasi [6] was closely matching with that of alloy 1 in this investigation.…”
Section: Potentiodynamic and Potentiostatic Testsupporting
confidence: 73%
“…The hardfacing alloys even at open-circuit potential are in the active state in high pH solutions. Although it has been shown through Pourbaix diagrams [11] that there is the formation of Cr 2 O 3 passive layer, it was argued that in order for the passive layer to form, Cr 7 C 3 should undergo dissociation. It was found that iron in the primary carbides provides some stability to the carbides.…”
Section: Stability Of Carbides Of Hcwi and Pourbaix Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCWI (sample area = 2.85 cm 2 ) was the working electrode exposed to electrolytes with selected pH, as shown in Table 3. pH 1.5, 2 and 7 were selected for explaining the trend of corrosion behaviour of HCWI in different regions of Pourbaix diagram of carbides [27,28]. Solutions with pH 1.5 and 2 were prepared from diluting sulphuric acid with distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Some investigators have used the Pourbaix diagrams of metals to explain the behaviour of corrosion of metals in natural sea water and aqueous sulfidic solution [25,26]. With this in view, Varmaa et al [27,28] developed Pourbaix diagrams for carbides in order to explain the trend observed in the corrosion behaviour of carbides. In this experimental study, the corrosion of hardfacing alloys based on HCWI, in acidic and neutral environments, will be explained through the use of Pourbaix diagrams of carbides.…”
Section: Introductionmentioning
confidence: 99%